Trigonometry 7th Edition

Published by Cengage Learning
ISBN 10: 1111826854
ISBN 13: 978-1-11182-685-7

Chapter 5 - Section 5.3 - Double-Angle Formulas - 5.3 Problem Set - Page 297: 48


See the steps.

Work Step by Step

$RHS =\dfrac{1-\tan^2 {\theta}}{1+\tan^2 {\theta}} =\dfrac{1-\tan^2 {\theta}}{\sec^2{\theta}}$ $RHS = \dfrac{1}{\sec^2{\theta}} - \dfrac{\tan^2{\theta}}{\sec^2{\theta}}$ $RHS = \cos^2{\theta} - \sin^2{\theta} = \cos{2\theta} = LHS$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.